2005
DOI: 10.1089/cap.2005.15.619
|View full text |Cite
|
Sign up to set email alerts
|

Zinc in Attention-Deficit/Hyperactivity Disorder

Abstract: Objective:The aim of this study was to review the published evidence for a role of zinc nutrition in attentiondeficit/hyperactivity disorder (ADHD). Method:A computer literature search was supplemented by the authors' knowledge. Results:Numerous controlled studies report cross-sectional evidence of lower zinc tissue levels (serum, red cells, hair, urine, nails) in children who have ADHD, compared to normal controls and population norms. A few studies show correlations of zinc level with either clinical severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(71 citation statements)
references
References 52 publications
2
65
0
4
Order By: Relevance
“…Zinc has numerous biological roles in the body and has strong antioxidant activity (Prasad 2014). Zinc deficiency and reduced zinc concentrations are often found in people with ADHD (Arnold and DiSilvestro 2005), and this has been confirmed in a meta-analysis by Scassellati and colleagues (2012). More recently, lowered vitamin D levels and vitamin D deficiency have also been reported in people with ADHD (Bener and Kamal 2014;Goksugur et al 2014).…”
Section: Potential Causes Of Oandns In Adhdmentioning
confidence: 88%
“…Zinc has numerous biological roles in the body and has strong antioxidant activity (Prasad 2014). Zinc deficiency and reduced zinc concentrations are often found in people with ADHD (Arnold and DiSilvestro 2005), and this has been confirmed in a meta-analysis by Scassellati and colleagues (2012). More recently, lowered vitamin D levels and vitamin D deficiency have also been reported in people with ADHD (Bener and Kamal 2014;Goksugur et al 2014).…”
Section: Potential Causes Of Oandns In Adhdmentioning
confidence: 88%
“…Apart from genetic factors, the status of mineral cofactors also appears to have an influence on the conversion and status of ω-3 fatty acids. Minerals such as magnesium [43] and zinc [8] are crucial desaturase enzyme cofactors. A lack of these micronutrients results in an inhibition of enzyme activity.…”
Section: Metabolism Of Pufas and Implications Of Metabolic Disordersmentioning
confidence: 99%
“…In 1996, Golub et al [32] reported attentional impairment at levels that did not cause growth retardation in moderately zincdeprived monkeys. Also many children with AttentionDeficit/Hyperactivity Disorder have reduced zinc levels compared to normal controls [33]. The non-significant changes in maximal saccadic velocity and saccadic deviation values in zinc group are in accordance with the nature and extension of these saccadic abnormalities in SCA2 patients.…”
Section: Discussionmentioning
confidence: 58%